Clinical and molecular characterization of burkholderia pseudomallei isolated from patients in Hospital Sultanah Nurzahirah (HSNZ) and treatment outcome - Mustapha, Faizah (2018)
Introduction Melioidosis is a potentially fatal disease caused by environmental saprophyte, Burkholderia pseudomallei. It is commonly found in soil and surface water in endemic regions of Southeast Asia and a common cause of community acquired sepsis and pneumonia in the east coast of Peninsular Malaysia. Methodology This is a prospective cohort study conducted to evaluate the demographic data, clinical features and treatment outcome of culture-proven melioidosis at Hospital Sultanah Nurzahirah, Terengganu from October 2016 till June 2017. Molecular confirmation of B. pseudomallei was performed using a PCR-based assay targeting sctQ gene of the TTS1 cluster. Twenty isolates were then subsequently genotyped using DNA sequencing of multiple gene loci to determine the genetic relatedness of the strains and to correlate the identified genotypes with clinical presentations and outcomes. The mortality rates of patients who receive early and appropriate empirical anti-melioidosis therapy was compared to those who did not receive appropriate empirical therapy. A total of 52 cases were included in the study. Patients’ clinical data were obtained from electronic clinical notes.Results Ninety six percent of melioidosis patients in this study had at least one underlying illness with the most common being diabetes mellitus. Bacteremic melioidosis was seen in most patients (n=48, 92.3%). Majority of them had bacteremic localized infection (57.7%), followed by disseminated bacteremia (26.9 %) and bacteremia with no focal lesion (7.7%). The remaining four patients (7.7%) had non bacteremic localized infection. Community acquired pneumonia and fever of unknown origin were the common presentation on admission. Lung was the most common organ involved (61.5%), followed by liver (15.4%), spleen, central nervous system and soft tissue (9.6%), joint and urinary tract (3.8%). All the culture-proven isolates were successfully confirmed with PCR. Constructed phylogenetic tree from sequencing of multiple gene loci revealed genetic diversity among B. pseudomallei strains, and there is no clustering seen with the clinical presentation or outcome. The overall mortality rate was 53.9% (n=28/52) and all patients who died had bacteremic melioidosis. Only 15 out of 52 patients (28.9%) were prescribed appropriate empirical antibiotics, with corresponding mortality of 26.7%. The mortality was significantly higher (64.9%) in those who did not receive appropriate empirical antibiotic therapy. Conclusion The clinical manifestations of melioidosis in Terengganu state were diverse and comparable to other countries worldwide. B. pseudomallei genotypes showed genetic diversity indicating distribution of different strains in the environment. The overall mortality rate is high, particularly in those who did not receive early and appropriate empirical antibiotics. Thus, a high index of suspicion in endemic country and the early use of appropriate empirical antibiotic therapy is crucial to prevent death.